2019
DOI: 10.1200/po.19.00001
|View full text |Cite
|
Sign up to set email alerts
|

Computed Tomography–Based Biomarker Outcomes in a Prospective Trial of Preoperative FOLFIRINOX and Chemoradiation for Borderline Resectable Pancreatic Cancer

Abstract: PURPOSE Effective preoperative regimens and biomarkers for pancreatic ductal adenocarcinoma (PDAC) are lacking. We prospectively evaluated fluorouracil, leucovorin, irinotecan, and oxaliplatin (FOLFIRINOX)-based treatment and imaging-based biomarkers for borderline resectable PDAC. METHODS Eligible patients had treatment-naïve, histology-confirmed PDAC and one or more high-risk features: mesenteric vessel involvement, CA 19-9 level of 500 mg/dL or greater, and indeterminate metastatic lesions. Patients receive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
22
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 18 publications
(22 citation statements)
references
References 37 publications
0
22
0
Order By: Relevance
“…Multiple studies have investigated the association between PDAC enhancement and clinical outcomes [10,11,[16][17][18]. Previously, we identified subtypes of PDAC tumors from diagnostic CT scans and demonstrated that in localized and metastatic human PDAC, visually scoring the change in enhancement on CT scans at the interface between the tumor and parenchyma (delta) was biologically and clinically relevant.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Multiple studies have investigated the association between PDAC enhancement and clinical outcomes [10,11,[16][17][18]. Previously, we identified subtypes of PDAC tumors from diagnostic CT scans and demonstrated that in localized and metastatic human PDAC, visually scoring the change in enhancement on CT scans at the interface between the tumor and parenchyma (delta) was biologically and clinically relevant.…”
Section: Discussionmentioning
confidence: 99%
“…nAUC significantly correlated with gemcitabine delivery, radiation response, stromal reaction, and clinical outcomes [5,6]. In addition, we showed that qualitative visual scoring of the change in enhancement on CT scans at the interface between PDAC tumors and parenchyma (delta) is biologically and clinically relevant, whereby tumors with a conspicuous border (high delta) possess lower degrees of stroma, show more aggressive mesenchymal biology, are more likely to have multiple common pathway mutations, and are associated with worse clinical outcomes compared to those with an inconspicuous border (low delta) [7][8][9][10][11]. However, in borderline cases, a qualitative classification can be challenging to the reader, and the presence of a quantitative metric that can objectively identify the delta class may help with clinical integration.…”
Section: Introductionmentioning
confidence: 99%
“…used mathematical modeling and clinical data to illustrate that controlling the growth rate of PDAC, especially at the early exponential phase, is more effective for prolonging patients’ survival than surgical resection ( 27 ). Since we previously observed multiple differences in the biology of high and low delta tumors ( 20 , 28 ), we hypothesized that the growth pattern and proliferation kinetics of these tumor subtypes would be fundamentally different. Our finding that the delta subtypes have differential growth rates aligns with our earlier observation regarding the morphological characteristics of the delta as a function of opposing proliferation versus migration mechanisms of tumors cells ( 19 ).…”
Section: Discussionmentioning
confidence: 99%
“…Previously, we identified imaging-based subtypes of PDAC (19). We showed that qualitative and quantitative scoring of the change in enhancement on CT-scans at the interface between PDAC tumors and parenchyma (delta) is biologically and clinically relevant, whereby tumors with a conspicuous border (high delta) on CT show more aggressive mesenchymal biology, are more likely to have multiple common pathway mutations, and are associated with poor clinical outcomes, when compared to those with an inconspicuous border (low delta) on CT (19)(20)(21)(22).…”
Section: Introductionmentioning
confidence: 99%
“…We seek to improve the precision with which all treatments are administered. One such method is through the use of radiomic signatures, which might ultimately be used to stratify patients into prognostic and treatment groups based on the degree of definition in the tumor–parenchyma interface and how this interface changes with preoperative therapy 68 . We completed a clinical trial that compared computed tomography between the baseline and after preoperative FOLFIRINOX and gemcitabine‐based CRT by designating the tumor–parenchymal interface as well‐defined or ill‐defined, and then observing stability or change over subsequent imaging.…”
Section: Recent Clinical Trials At MD Anderson and Future Directionsmentioning
confidence: 99%